Allosteric Modulators of Sigma-1 Receptor: A Review - Vavers, Edijs; Zvejniece, Liga; Maurice, Tangui; Dambrova, Maija (Frontiers in Pharmacology, 2019)
Although a native ligand for sigma-1 receptor (Sig1R) has not been identified thus far, allosteric modulators of Sig1R are described as compounds that can increase the activity of some Sig1R ligands that compete with (+)-pentazocine, one of the classic prototypical ligands that binds to the orthosteric Sig1R binding site. Sig1R is an endoplasmic reticulum membrane protein that, in addition to its promiscuous high-affinity ligand binding, has been shown to have chaperone activity. Different experimental approaches have been used to describe and validate the activity of allosteric modulators of Sig1R. Sig1R-modulatory activity was first found for phenytoin, an anticonvulsant drug that primarily acts by blocking the voltage-gated sodium channels. Accumulating evidence suggests that allosteric Sig1R modulators affect processes involved in the pathophysiology of depression, memory and cognition disorders as well as convulsions. This review will focus on the description of selective and nonselective allosteric modulators of Sig1R, including molecular structure properties and pharmacological activity both in vitro and in vivo, with the aim of providing the latest overview from compound discovery approaches to eventual clinical applications. In this review, the possible mechanisms of action will be discussed, and future challenges in the development of novel compounds will be addressed.